Prevalence and prognostic impact of BRAF V600E mutation and CDKN2A deletion in pediatric high-grade glioma - Karim, Soha; Mosaab, Amal; Taha, Hala; Naguib, Iman; Refaat, Amal; Maher, Eslam; Zaghloul, Mohamed Saad; El-Beltagy, Mohamed; Hafez, Hanafy; Kamal, Mohamed; Salem, Sherine; Kieran, Mark W.; et al. (Frontiers in Oncology, 2025)
Background and aimPediatric high-grade glioma (pHGG) is a rare and challenging disease with dismal outcomes. Identifying prognostic markers and targeted therapeutic avenues is crucial.MethodsWe conducted a retrospective study involving 130 pediatric patients with HGG treated at the Children’s Cancer Hospital Egypt between July 2007 and December 2018. Demographic, clinical, and molecular data were collected, and BRAF V600E mutation and CDKN2A deletion status were assessed.ResultsTumor site, and extent of resection significantly influenced outcomes (P value 0.001 for both). Out of 130 patients, 128 underwent BRAF analysis and 7% harbored the BRAF V600E mutation (n:9) and 129 patients underwent CDKN2A analysis. Of those, 78 patients (60%) had CDKN2A deletion, 18 patients had homozygous CDKN2A deletions, and the remaining 60 patients had heterozygous deletions. BRAF V600E mutation and CDKN2A status (deleted vs normal) did not affect the outcome (p value 0.46 and 0.23, respectively). The 3 years Overall survival and Progression free survival rates were 26.2% and 23.4%, respectively.ConclusionNeither BRAF V600E mutation nor CDKN2A deletion status significantly impacted this cohort’s progression-free survival (PFS). Patients with these mutations now have access to new targeted BRAF V600E inhibitors, which may improve their outcomes.